Ending Poverty: Islamic Solutions For The Welfare of The Ummah - Wahyudi, Ickhsanto; Mahroji, Mahroji; Angelita, Julya (SENTRALISASI, 2024)
Poverty is a social problem of global concern. In developing countries including Indonesia, tens of millions of people live below the poverty line. In Islam, poverty is seen as a form of social injustice that must be resolved. The Quran and Hadith explicitly indicate the duty of Muslims to help the poor. This paper aims to analyze the Islamic perspective on poverty and propose Islamic solutions to achieve the welfare of the Ummah, within the framework of achieving maqashid sharia.  The method used is a literature study of Islamic sources and contextual analysis of the poverty situation in Muslim countries. The results show that poverty is caused by various factors, both internal and external. Islam offers comprehensive solutions such as the Islamic economic system, optimization of zakat and waqf, policy reform, and others. This is important in order to realize the purpose of sharia to protect the lives, property, and benefit of the people. However, its implementation needs to be studied further so that it is right on target in alleviating poverty in the contemporary Islamic world.